Current management of upper lid ptosis: a web-based international survey of oculoplastic surgeons - Alicia Galindo‐Ferreiro; Denise de Cássia Moreira Zornoff; Jose Eduardo Correntes; Patrícia Akaishi; Silvana Artioli Schellini (2022)
Common complications comprised undercorrection after levator resection (40%) or frontalis suspension (27.5%).Conclusions: This study reports the current practice patterns among Spanish and Latin American oculoplastic surgeons in upper lid ptosis diagnosis and treatment.Surgeons can use this study data to compare disease management with their colleagues.